Awareness and practices regarding zoonotic influenza prevention in Romanian swine workers. (December 2013) - Rabinowitz, Peter M.; Huang, Eileen; Paccha, Blanca; Vegso, Sally; Gurzau, Anca
Abstract : Background: Swine workers may play a key role in transmission of zoonotic influenza viruses. At the same time, little is known about the extent and effectiveness of influenza prevention programs for these at‐risk workers. Objectives: To characterize practices and attitudes regarding zoonotic influenza transmission among swine workers in Romania. Methods: We conducted a convenience survey of swine workers in Romania. The confidential survey included questions about awareness of zoonotic influenza risk, work tasks performed, flu vaccination status, and reported influenza‐like illness. Results: A total of 103 workers at seven farms completed the survey. The percentage of workers reporting concern about either contracting influenza from pigs or giving influenza to pigs was 78% and 70%, respectively. Although 60% of workers reported having a sick‐leave policy at work, only 7% of workers reported receiving seasonal influenza vaccination during the past flu season. Only 5% of the workers reported flu‐like illness during the past year while 3% of workers reported that pigs appeared sick with influenza over the same time period. The majority of workers reported using protective overalls and rubber boots during swine work, with lower rates of use of gloves. Reported use of respiratory protection was rare, and use of any personal protective equipment did not differ when pigs appeared ill. Conclusions: Despite awareness and concern regarding zoonotic influenza, Romanian swine workers report low rates of influenza vaccine or respiratory protection. As part of global pandemic influenza preparedness, enhanced prevention programs for swine workers should address such gaps.